Young people, Malay and English in multilingual Singapore. Issue 3 (September 2014) - CHONG, EUVIN LOONG JIN; SEILHAMER, MARK F.; BOLTON, KINGSLEY; NG, BEE CHIN
ABSTRACT With English use extremely prevalent in Singapore, young Singaporeans are increasingly abandoning the use of their ethnic languages. The Singapore Malay community, however, is frequently depicted as an exception to this trend, proudly keeping Malay as their dominant language and an integral part of their cultural identities despite the overwhelming dominance of English in present day Singaporean society. This study seeks to obtain a sense of whether this is indeed the case by investigating the relationships Singaporean Malay university students (ages 18–26) have with Malay along the dimensions of language expertise, language inheritance, and language affiliation. Fifty survey participants reported on their proficiency in, use of, and perceptions of Malay and English. The results indicate that participants' relationships with Malay are indeed strongly characterized by all three dimensions – expertise, inheritance, and affiliation – despite their prevalent use of English in all but a few domains and, by the majority, identification of English as the language that best defines them as Singaporeans.